Emerging Trends and Advancements in Pharmaceutical FormulationsTechnologies - Nelluri, Dr Kanaka Durga Devi (Asian Journal of Pharmaceutics (AJP), 2024)
The field of pharmaceutics has seen remarkable advancements in recent years, driven by technological innovations, novel drug delivery systems, and a deeper understanding of drug physicochemical properties. This review highlights the latest developments in pharmaceutics, encompassing drug delivery systems, formulation strategies, and emerging trends. Advanced drug delivery systems, including nano-based carriers and stimuli-responsive platforms, offer precise control over drug release and targeting. Formulation strategies such as solid dispersion technology and lipid-based formulations improve drug solubility and bioavailability. Emerging trends focus on sustainable drug delivery using natural polymers, personalized medicine based on pharmacogenomics, and continuous manufacturing techniques. The integration of interdisciplinary approaches, such as nanotechnology and biotechnology, is driving innovation in pharmaceutical formulations. Overall, these advancements hold promise for enhancing therapeutic efficacy, patient compliance, and addressing medical needs, driving the field of pharmaceutics toward transformative growth